The Changing Landscape of Diffuse Low Grade Glioma (DLGG) Management in the West of Scotland: A Single Centres 10-Year Experience. (1st October 2022) - Tilling, Elliot; Lammy, Simon; Bridgman, Elsie; Johnson, Hannah; Stan, Alexandru; Taylor, Aaron; Grivas, Athanasios
Abstract: AIMS: Management strategies for patients diagnosed with diffuse low grade glioma (DLGG) remain controversial. Current evidence favours resection over biopsy. This has resulted in more aggressive intervention. We examined management trends in the West of Scotland over a 10 year period. METHOD: Patients diagnosed with DLGG between 2010 and 2019 were included and grouped according to time of diagnosis: 1) 2010-2012, 2) 2013-2016 and 3) 2017-2019. Clinical characteristics, management and overall survival (OS) were investigated and comparatively analysed. Survival between resection and biopsy groups was also analysed. RESULTS: 84 patients were included (n=25 in Group 1, n=35 in Group 2 and n=24 in Group 3). Biopsy was less commonly performed in Group 2 (17%) and Group 3 (21%) compared to Group 1 (56%) p=0.014. The frequency of post-operative seizures: G1: n=3 (12%), G2: n=1 (2.9%), G3: n=2 (8.3%) (p=0.385) and focal neurological deficit: G1: n=4 (16%), G2: n=8 (22.9%), G3: n=6 (25) (p=0.718) and mean length of stay (LoS) in days: G1: 7.7, G2: 8.8, G3: 7.4 (p = 0.548) were similar across the groups. Survival analysis revealed no significant difference between groups: G1 52%, G2 69%, G3 75% (p=0.172). Patients managed by resection (n=58) versus biopsy (n = 26) observed improved survival (resection OS 70% compared to biopsy OS 39% (p= 0.005)). CONCLUSION: Resection results in improved survival over biopsy. This has resulted in an institutional change over time. But no significant difference was observed in OS between different time periods.